Associations between vitamin D and pulmonary function in chronic spinal cord injury. (4th March 2019) - Garshick, Eric; Walia, Palak; Goldstein, Rebekah L.; Teylan, Merilee A.; Lazzari, Antonio A.; Tun, Carlos G.; Hart, Jaime E.
Abstract : Context/Objective: Individuals with chronic spinal cord injury (SCI) have an increased risk of morbidity and mortality attributable to respiratory diseases. Previous studies in non-SCI populations suggest that vitamin D may be a determinant of respiratory health. Therefore, we sought to assess if lower vitamin D levels were associated with decreased pulmonary function in persons with chronic SCI. Design: Cross-sectional study. Setting: Veterans Affairs Medical Center. Participants: 312 participants (260 men and 52 women) with chronic SCI recruited from VA Boston and the community participating in an epidemiologic study to assess factors influencing respiratory health. Methods: Participants provided a blood sample, completed a respiratory health questionnaire, and underwent spirometry. Linear regression methods were used to assess cross-sectional associations between plasma 25-hydroxyviatmin D and spirometric measures of pulmonary function. Outcome Measures: Forced expiratory volume in one second (FEV1 ), forced vital capacity (FVC), and FEV1 /FVC. Results: Adjusted and unadjusted for a number of confounders, there was no significant association between plasma vitamin D levels and FEV1, FVC, or FEV1 /FVC. For example, in fully adjusted models, each 10 ng/ml increase in vitamin D was associated with a 4.4 ml (95%CI −64.4, 73.2, P = 0.90) ml change in FEV1. Conclusion: There was no significant cross-sectional association between plasma vitamin D and FEV1, FVC, or FEV1 /FVC in this cohort of individuals with chronic SCI.